Factors affecting local regrowth after watch and wait for patients with a clinical complete response following chemoradiotherapy in rectal cancer (InterCoRe consortium): an individual participant data meta-analysis. (December 2018) - Chadi, Sami A; Malcomson, Lee; Ensor, Joie; Riley, Richard D; Vaccaro, Carlos A; Rossi, Gustavo L; Daniels, Ian R; Smart, Neil J; Osborne, Melanie E; Beets, Geerard L; Maas, Monique; Bitterman, Danielle S; et al.
Summary: Background: In patients with rectal cancer who achieve clinical complete response after neoadjuvant chemoradiotherapy, watch and wait is a novel management strategy with potential to avoid major surgery. Study-level meta-analyses have reported wide variation in the proportion of patients with local regrowth. We did an individual participant data meta-analysis to investigate factors affecting occurrence of local regrowth. Methods: We updated search results of a recent systematic review by searching MEDLINE and Embase from Jan 1, 2016, to May 5, 2017, and used expert knowledge to identify published studies reporting on local regrowth in patients with rectal cancer managed by watch and wait after clinical complete response to neoadjuvant chemoradiotherapy. We restricted studies to those that defined clinical complete response using criteria equivalent to São Paulo benchmarks (ie, absence of residual ulceration, stenosis, or mass within the rectum on clinical and endoscopic examination). The primary outcome was 2-year cumulative incidence of local regrowth, estimated with a two-stage random-effects individual participant data meta-analysis. We assessed the effects of clinical and treatment factors using Cox frailty models, expressed as hazard ratios (HRs). From these models, we derived percentage differences in mean θ as an approximation of the effect of measured covariates on between-centre heterogeneity. This study is registered with PROSPERO, number CRD42017070934. Findings: We obtained individual participant data from 11 studies, including 602 patients enrolled between March 11, 1990, and Feb 13, 2017, with a median follow-up of 37·6 months (IQR 25·0–58·7). Ten of the 11 datasets were judged to be at low risk of bias. 2-year cumulative incidence of local regrowth was 21·4% (random-effects 95% CI 15·3–27·6), with high levels of between-study heterogeneity ( I 2 =61%). We noted wide between-centre variation in patient, tumour, and treatment characteristics. We found some evidence that increasing cT stage was associated with increased risk of local regrowth (random-effects HR per cT stage 1·40, 95% CI 1·00–1·94; ptrend =0·048). In a subgroup of 459 patients managed after 2008 (when pretreatment staging by MRI became standard), 2-year cumulative incidence of local regrowth was 19% (95% CI 13–28) for stage cT1 and cT2 tumours, 31% (26–37) for cT3, and 37% (21–60) for cT4 (random-effects HR per cT stage 1·50, random-effects 95% CI 1·03–2·17; ptrend =0·0330). We estimated that measured factors contributed 4·8–45·3% of observed between-centre heterogeneity. Interpretation: In patients with rectal cancer and clinical complete response after chemoradiotherapy managed by watch and wait, we found some evidence that increasing cT stage predicts for local regrowth. These data will inform clinician–patient decision making in this setting. Research is needed to determine other predictors of a sustained clinical complete response. Funding: None.